2011
DOI: 10.1016/j.bbi.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Altered immunoglobulin profiles in children with Tourette syndrome

Abstract: BACKGROUND-Post-infectious autoimmunity and immune deficiency have been implicated in the pathogenesis of Tourette syndrome (TS). We asked here whether B cell immunity of patients with TS differs from healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…In keeping with Landau et al (2012), this study found elevated levels of IgG4, bolstering evidence for a drive toward autoimmune disturbance. A trend toward an increase in IgG1 during tic exacerbations was found in a prospective analysis in the same study (Bos-Veneman et al, 2011). IgA dysgammaglobulinemia has been reported in another study of children with TS.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…In keeping with Landau et al (2012), this study found elevated levels of IgG4, bolstering evidence for a drive toward autoimmune disturbance. A trend toward an increase in IgG1 during tic exacerbations was found in a prospective analysis in the same study (Bos-Veneman et al, 2011). IgA dysgammaglobulinemia has been reported in another study of children with TS.…”
Section: Introductionsupporting
confidence: 58%
“…Another study reporting elevated IgE levels in subjects with TS additionally noted elevated levels of IgG4 (Landau et al, 2012), consistent with a possible vulnerability to the development of autoimmune disease (Takahashi et al, 2010). In contrast, one report based on two independent cross-sectional study samples noted that IgE serum levels tended to be decreased in one of the two samples, and also reported decreased levels of IgG3 and a trend toward a decrease in IgM levels (Bos-Veneman et al, 2011). In keeping with Landau et al (2012), this study found elevated levels of IgG4, bolstering evidence for a drive toward autoimmune disturbance.…”
Section: Introductionmentioning
confidence: 92%
“…In particular, the risk for TS has been shown to be significantly enhanced in patients with a history of adverse events and/or stress in the prenatal and perinatal period (Leckman et al, 1990; Motlagh et al, 2010; Bos-Veneman et al, 2011), as well as maternal smoking (Mathews et al, 2006). Given that obstetric complications and maternal smoke have been linked to multiple mental disorders, several animal models have been developed in the attempt of reproducing the pathophysiological sequence leading to their sequelae (Boksa, 2004; Yochum et al, 2014).…”
Section: Animal Models Based On Environmental Etiologymentioning
confidence: 99%
“…A subsequent study suggesting that GTS individuals have immune deficiency was that of an immunoglobulin: Bos-Veneman et al 71 demonstrated that at least some GTS patients have decreased IgG3 and possibly also low IgM levels, although only a few subjects had Ig immunodeficiency 71. Another study showed that patients with GTS when compared with controls had higher rates of IgA/IgG antibody titres to Chlamydia trachomatis and a trend with Toxoplasma gondi 72 and Mycoplasma pneumoniae 73 with the authors suggesting that infections contribute to GTS by triggering an immune response.…”
Section: Aetiological Theoriesmentioning
confidence: 99%